Fraud prevention strategies: the perception of Saudi Arabian banks employees - Ali Hakami, Tahani; Mohd Mohid Rahmat, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The main objective of the study is to examine the perceptions of employees of banks operating in Saudi Arabia on the effectiveness of fraud prevention. A total of 150 questionnaires are distributed among employees of 12 Saudi banks with a response rate of 53.3 %. These fraud prevention strategies are classified using Cressey’s fraud triangle which consists of pressure, rationalization and opportunity. The research engaged quantitative research method using questionnaire. The findings indicate that all strategies are perceived to be highly effective with strategies under the opportunity category turned out to be the most effective. However, when detailed analyses of the practices are compared across selected characteristics, various perceptions are revealed. Positive employee recognition, ethics training, imposing penalty, fraud auditing, and disciplinary action are perceived differently between male and female employees. Female employees perceive these fraud prevention policies and strategies as more effective than male employees. On the other hand, the differences in perception is found to be insignificant for working experience, qualifications, accounting experience, age group, job titles, and departments.